Influencia de las actividades laborales de la EMAARS-EP-Ángel Pedro Giler en la seguridad y salud ocupacional - Quiroz Carranza, Paola Katherine (2015)
The purpose of this research was to determine the influence of industrial activities in the EMAARS-EP, and the quality of occupational safety and health. This research establishes occupational hazards on workers, when carrying out their activities. For the development of this thesis, surveys and interviews were determined in the departments of general management, legal management, financial administrative management, technical management and e-marketing, later it was developed a flowchart of inputs and outputs of the purification process. Labor quality was analyze through risk matrix per job of the ministry of labour relations, it determined and described mechanical, physical, biological and psychosocial risk factors. A plan for occupational safety and health was based on the regulations of the executive order and safety 2393 for workers health and work environment improvement; regulation of general insurance on risk job resolution 390, whereby the latent occupational risks are minimized; to which workers are exposed in the company.